If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -4(y + -1) + 3 = 0 Reorder the terms: 6y + -4(-1 + y) + 3 = 0 6y + (-1 * -4 + y * -4) + 3 = 0 6y + (4 + -4y) + 3 = 0 Reorder the terms: 4 + 3 + 6y + -4y = 0 Combine like terms: 4 + 3 = 7 7 + 6y + -4y = 0 Combine like terms: 6y + -4y = 2y 7 + 2y = 0 Solving 7 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2y = 0 + -7 2y = 0 + -7 Combine like terms: 0 + -7 = -7 2y = -7 Divide each side by '2'. y = -3.5 Simplifying y = -3.5
| 2x+3-7x=28 | | 4x=11+1 | | 2.2k-4.3=12.6k+14.5 | | 3x+5-x=x+5 | | 2a+6+3a=16 | | 4x+33+6x+5=360 | | 4(5x+1)+4(x-3)= | | 11x-19y=-7 | | 7y-21=-8y | | 4x=3+10 | | 2(x+3)=18-6x | | v^3+8=0 | | 90x-1.5x^2=1200000 | | 2.2x+0.4=2(1.1x-0.1) | | 14x+6+10x+6=180 | | 7y+21=-8y | | 25x^2-95x+61=0 | | 2+7x=20x | | 3x-3*x-3=2x-1*2x-1*2x | | -5x-(6x-3)=-8x+27 | | -t+47282=4848235 | | -8(1-7n)-1=-9+8n | | 7x-15=11+5x | | -10c=-40 | | 7x+9x=20 | | -42x-6=42x+7+6 | | 3/7=p-1/7 | | 60a^3b-52a^2b+8ab= | | 9x+8=6x+7 | | 10-10x=23-17 | | 16x^2+40x+16=-9 | | 7=3(-6x+7) |